EMPOWERING MINDS IN THE DIGITAL AGE: UNLEASHING THE POWER OF DIGITAL LITERACY - Che Wan Muhammad Arif Rifqi bin Che Wan Jaafar; Erdania Putri binti Shahrul Azman; Nur Aiman bin Ash; Tengku Nur Azilah Akma binti Tengku Jelani; Najatul Afiqah Binti Mohd Affandi (International Journal of Accounting, Finance and Business, 2023)
The potential to use technology effectively and operate the constantly evolving digital environment of today is becoming more and more important. The ability to operate and communicate with digital tools successfully has become more important for success and strength in the modern world. This ability is known as digital literacy. In this paper, the idea of digital literacy as a potent enabler of empowerment in the digital age is explored. It explores the many dimensions of digital literacy, including critical thinking, information evaluation, communication, and challenges in addition to technical skills. This paper also discussed the importance of digital literacy in education for the purpose of encouraging students to be able to navigate efficiently in the digital society to achieve academic excellence.